Pengaruh Kapasitas Sumber Daya Manusia, Pemanfaatan Teknologi, Pengelolaan Aset terhadap Kualitas Laporan Keuangan Pemerintah Daerah dengan Sistem Pengendalian Intern dan Komitmen Organisasi sebagai Variabel Moderating (Studi pada OPD Kabupaten Rokan Hilir) - Redian Mulyadati; Vince Ratnawati; Alfiati Silfi (Jurnal Ekonomi, 2019)
The objectives of this research are to investigate the effects of relationship between human resource capacity, technology utilization, asset management against the quality of local government financial reports; internal control systems and organizational commitments as moderating variables (study in OPD regency of Rokan Hilir). The data in this study were obtained from a questionnaire that had been filled by 115 respondents of civil servants in the Regency of Rokan Hilir. Data processed using moderate regression analysis (MRA) & multiple linear regression analysis by using IBM SPSS Version 21. The result of research shows that is a significant effect of human resource capacity, technology utilization and asset management on the quality of the financial statements of the local government of Rokan Hilir Regency with Pvalue < alpha 0.05 value of 0.000, 0.000, 0.004. We also found that internal control system variable moderates the effect of human resource capacity, technology utilization and asset management on the quality of the financial statements of the local government Regency of Rokan Hilir with Pvalue < alpha 0.05 values of 0.010, 0.000, 0.000. And organizational commitment variable moderates the influence of human resource capacity, technology utilization and asset management on the quality of the financial statements of the local government Regency of Rokan Hilir with Pvalue < alpha 0.05 values of 0.000, 0.000, 0.000.